Nanotechnology: A boon in cancer therapy: Review - Sonia Sangwan; Raman Seth (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2021)
In cancer, there is uncontrolled cell division, which results in invasion and metastasis. Carcinomas are a significant cause of mortality worldwide. Recently, radiotherapy and chemotherapy are the primary treatment measures that are being used to destroy cancer cells. However, these modalities kill normal cells of the body, along with the destruction of cancer cells. This non-specific action is harmful to the whole body, which results in the loss of hairs, anemia, and weakness in the body. Pathological features of tumors and their abnormal neo-angiogenesis also reduce the efficiency of conventional cancer treatment. Nanoparticles (NPs) have been considered outstanding cancer-targeting vehicles due to their small size, ability to load various drugs and large surface area, and increased absorption of conjugates. They are designed and developed to take advantage of a malignant tumor's morphology and characteristics, benefits of leaky tumor vasculature, specific cell surface antigen expression, and rapid proliferation. The recent nanoscale vehicles include liposomes, polymeric nanoparticles, magnetic nanoparticles, dendrimers, and nanoshells; lipid-based NPs have been used as conjugates.